The Effect of Compensation, Job Satisfaction, and Career Development on the Auditors' Performances and P2UPD Regional Inspectorate of Pohuwato Regency - Jeffry Junyar Saehu; Arifin Tahir; Frista Iin Wahyuni (Jurnal Ilmu Manajemen dan Bisnis, 2021)
ABSTRACT This study aims to determine and analyze the effect of compensation, job satisfaction and career development on the Performance of the Auditor and P2UPD Regional Inspectorate of Pohuwato Regency. This research uses descriptive quantitative method. The population and sample in this study were the staff of the Regional Inspectorate of Pohuwato Regency. Data analysis used multiple regressions. The results show that compensation has a significant effect on performance, job satisfaction has a significant effect on performance, career development has a significant effect on performance and compensation, job satisfaction and career development simultaneously have a positive and significant effect on performance.